PENGARUH PENGENDALIAN INTERNAL DAN KESESUAIAN KOMPENSASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI PADA PEMERINTAH DAERAH KABUPATEN SRAGEN (Studi Kasus pada Badan Pendapatan Pengelolaan Keuangan dan Aset Daerah) - Wulansari, Ayu; Rispantyo, Rispantyo; Kristianto, Djoko (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of this study was to determine the effect of internal control and the suitability of compensation for the tendency of accounting fraud in Sragen district government. The sample of this study was 85 respondents consisting of employees from the secretariat, the field of billing and reporting, the area of income and regional cash management, the field of accounting, the area of regional asset management, the field of budget. Data collection techniques using questionnaires. Data analysis techniques used are descriptive analysis, test instruments, test classic assumptions and test hypotheses. The results of this study indicate that internal control and suitability of compensation have a significant positive effect on the tendency of accounting fraud in Sragen district government.